Microstructure and wear properties of AISI 1020 steel surface modified by HARDOX 450 and FeB powder mixture - Teker, Tanju; Karatas, Selcuk; Yilmaz, S. Osman (Maik Nauka/Interperiodica/Springer, 2014)
The effects of gas tungsten arc-processing (GTA) was used for developing wear resistance of AISI 1020 steel substrate. Appropriate quantities of FeB powder and Hardox 450 were combined to create conditions that synthesize particles into reinforced Fe-based composite surface coating. The phase transformations on new created coated surfaces were comprehensively examined by using a combination of scanning electron microscopy (SEM), microanalysis by energy dispersive spectrometry (EDS), X-Ray diffraction (XRD), microhardness and abrasive wear tests. The microstructure studies of the superficial layers of the coating revealed presence of a mixture of the dendritic phase structure of ferrit (alpha) and FeB-Fe2B-Fe3B borides. The results show that; the size of dendrites formed in the coated surface, the change of hardness of the coated surfaces, the borides volume rate and thickness of the coating changed by the variation of the processing parameters. The studies concluded that Hardox 450 + 40 wt % FeB composite coating was the most appropriate combination in terms of hardness and wear performance.
Keywords: Boride Layers; Carbon Steel